Membangun Kesadaran Masyarakat Mengenai tradisi Pernikahan di Bawah Umur Terhadap Hak Anak - Edwin Hadiyan (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2017)
The article discuss about a phenomena of early age marriage which is interesting to modern scholars, because it is happen factually and appearing many problems either in social life or law. So, it becomes the hot and controversial issue, especially about its relationship to Islamic Law and National Law. Particularly, the discussion is regarding topics, such as: the rights of child, the problems of reproduction, life after marriage, unwed pregnancy, and so on. Within presenting some phenomena which were happen, the article concludes and relates it to some social theories and Islamic doctrines, in order to present the problem and solutions together. It gives the new horizon of thought in the topic.